Assessment of Ischemic Index in Retinal Vascular Diseases Using Ultra-Wide-Field Fluorescein Angiography: Single Versus Summarized Image. (4th May 2017) - Franco-Cardenas, Valentina; Shah, Sanket U.; Apap, David; Joseph, Anthony; Heilweil, Gad; Zutis, Kris; Trucco, Emanuele; Hubschman, Jean-Pierre
ABSTRACT: Background and Objective : To compare a single image with a computer-generated summarized image from the ultra-wide-field fluorescein angiogram (UWFFA) sequence for evaluation of ischemic index (ISI). Materials and Methods : UWFFA sequences from patients with diabetic retinopathy (DR) (n=5), branch retinal vein occlusion (BRVO) (n=5), and central retinal vein occlusion (CRVO) (n=5) were evaluated by six graders. A single image best illustrating retinal non-perfusion was compared to a summarized image generated by computerized superimposition of angiograms. Non-perfused and ungradable retinal areas were outlined and the ISI between the single and summarized images was compared. Results : The mean ISI in the single versus (vs) summarized images was 17% vs 15% in BRVO (p=0.12), 48% vs 48% in CRVO (p=0.67), and 25% vs 23% in DR (p=0.005). Inter-grader agreement of ISI in single versus summarized images was 0.43 vs 0.40 in BRVO, 0.69 vs 0.71 in CRVO, and 0.53 vs 0.34 in DR. Conclusion : Computer-generated summarized images were similar to single images for grading ISI in BRVO and CRVO, but underestimated it in DR.